Evaluation of crime prevention initiatives: the principles of evaluation - Wijckmans, Belinda (Thematic paper, 2013)
The fifth thematic paper in the series published by the EUCPN Secretariat in collaboration with the Irish Presidency, focuses on the theme of evaluation. It is written in the framework of the third EUCPN Toolbox on the same theme. The toolbox is developed to assist people engaged in evaluation who have limited resources, who often lack the internal expertise to conduct a robust evaluation or who have limited access to information and external support. The aim of this instrument is to develop more insight in ‘how and why’ to evaluate and to provide a minimum standard of knowledge and skills who are (about to be) involved in programme evaluation of small scale community-based crime prevention initiatives. Attention is paid to the planning of an evaluation, the data collection and analyses, and the communication of results. This thematic paper aims to be a general introduction to the principles of evaluation based on existing academic literature and provides more detailed information about the second part of the toolbox, the practical guidelines. It is recommended to read the thematic paper in conjunction with the guidelines in the toolbox.